Genetic studies on the inheritance of disease resistance, fruit yield and quality in tomatoes (Lycopersicon esculentum Mill) - Frimpong, Adams (2012)
A thesis submitted to the Crop Science Department, College of Agriculture and Natural Resources, Kwame Nkrumah University Of Science & Technology, Kumasi, in partial fulfilment of the requirements for the Master of Philosophy Degree in Plant Breeding.